STRUKTUR KOMUNITAS IKAN HASIL TANGKAPAN JARING INSANG DI SUNGAI BATANG TEBO DESA BUNGKAL KECAMATAN TEBO TENGAH KABUPATEN TEBO - Abdurrahman Madani; Nurhayati Nurhayati; Mairizal Mairizal; Lisna Lisna; M Hariski; Indra Sulaksana (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2022)
One of the largest tributaries in the Batanghari area is the Batang Tebo River which passes through Bungkal Village. Currently, the Batang Tebo River is a place for waste disposal, garbage, oil spills, and even the biggest illegal gold mining (PETI). This resulted in a drastic decrease in fishermen in Batang Tebo waters using gill nets. The purpose of the study was to determine the structure of the fish community in Batang Tebo from the catch when using gill nets. This research was started on April 18, 2022 - May 31, 2022, and is located on the Batang Tebo River, Bungkal Village, Tebo Regency. The researcher thus causes the survey method and random sampling as the data collection. Collection of data from this research activity included the structure of the community caught by fishermen using gill nets. The catch data includes fish size, fish weight, total fish weight, and the fish species. The supporting data collect environmental parameters (temperature, pH, current speed, brightness). The number of fish catches produced during the research activity reached 292, with the composition of the catch consisting of 5 species, namely: Baung Fish (Hemibagrus Menerus), Sand Lambak Fish (Labiobarbus Festivus), Lais Fish (Cryptopterus Sp), Kapiat Fish (Barbonymus schwanenfeldi), Juaro Fish (Pangasius polyuranodon). The highest catch was Baung fish many as 89 fish lowe catch was Juaro fish as many as 17 dominant index was 0.23. Community structure of fish caught by Baung Fish, Flat Lambak Fish, Lais Fish, Kapiat Fish, and Juaro Fish. Community structure of fish caught by Baung Fish, Flat Lambak Fish, Lais Fish, Kapiat Fish, juror fish. With diversity with medium, uniformity with (high), on dominance with (low), there are fish that dominate in the catch and are also supported by environmental parameters in the form of temperature, pH, brightness, and speed of current.